Natural Flocculation with Tara (Caesalpinia spinosa) as a Sustainable Strategy to Reduce Turbidity in the Chonta River - Poma de la Cruz, Paulo Cesar; Licapa – Redolfo, Gladys S.; Díaz Guerrero, Jhenyfer Jhanela; Aceijas Diaz, Ronal Greiner; Vega - Eras, Maryuri (LACCEI, 2025)
The present study evaluated the effectiveness of the natural flocculant based on tara (Caesalpinia spinosa) as a sustainable alternative for turbidity removal in contaminated water. Treatment conditions were analyzed in two sedimentation intervals, 15 and 30 minutes, using a 200-mesh sieve and three stages: rapid mixing at 200 rpm for 2 minutes, slow mixing at 40 rpm for 20 minutes, and floc sedimentation for the specified time. Different concentrations of tara (Caesalpinia spinosa) were tested. At the 15-minute interval, the samples showed an initial turbidity removal of 9.60%, reducing the average from 62.5 NTU to 56.5 NTU. A gradual increase in treatment efficiency was observed, achieving a significant removal of 58.56%, with residual turbidity values as low as 25.9 NTU. In cases of higher concentration, the maximum recorded removal was 61.60%, with a residual turbidity of 29 NTU, suggesting a saturation point where higher concentrations do not produce significant improvements. At the 30-minute interval, the results showed greater efficiency in turbidity removal. The samples reduced turbidity by up to 42.68%, reaching values of 37.2 NTU in the initial concentrations. The efficiency progressively increased, achieving a removal of 73.60%, with residual turbidity of 16.5 NTU. In the most effective treatments, the maximum removal reached 80.16%, with a residual turbidity of 12.5 NTU, highlighting that longer sedimentation times improve the results. These findings confirm that the tara flocculant is effective for turbidity removal, especially in extended sedimentation intervals, positioning it as a viable and cost-effective solution for contaminated water treatment.